Ameliorating potential of Auricularia auricula-judae polysaccharides in mitigating hypercaloric diet-induced behavioral disorders through gut microbiota regulation - Fei, Yujie; Zhang, Jingwen; Yuan, Sijia; Liu, Ye; Wang, Xiaoru; Wang, Meng; Zhao, Haoan; Liu, Qian (Frontiers in Nutrition, 2025)
As a major nutraceutical component of a traditional edible fungus Auricularia auricula-judae, Auricularia auricula-judae polysaccharide (AAP) has been well-documented due to its outstanding hypolipidemic and hypoglycemic bioactivities. This study investigated the effects of AAP on hypercaloric diet-induced cognitive dysfunction in mice and the underlying mechanisms. Behavioral and histological results demonstrated that AAP could ameliorate high-fat and high-fructose diets (HFFD)-induced memory impairment and neuronal loss. AAP significantly inhibited inflammatory responses and balanced oxidative stress states in mice brain and colon tissues. AAP dietary supplements remarkably reshaped gut bacteria composition. The abundance of Dubosiella, Bacteroides, and Parasutterella were significantly increased. Differential bacteria abundance showed a strong correlation with behavioral related indicators, inflammatory factors, antioxidant enzymes and serum metabolites levels. These results suggest that AAP is able to ameliorate high-calorie diet-induced cognitive dysfunction in mice, as well as modulate the regulation of gut flora homeostasis and serum metabolites in mice. And these results are of positive significance for promoting the utilization of Auricularia auricula-judae resources and for the development of nutraceutical products in the brain with AAP as the primary active component.